Monitoring efek samping obat antituberkulosis fase intensif dan lanjutan pasien dewasa tuberkulosis di RSUD Kota Bandung - Siti Thannisa Aisiyah Gumanti; Dhigna L. C. P.; Via Rifkia (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis which can be transmitted through sputum splashes. The use of antituberculosis drugs can cause a variety of side effects depending on the duration of TB treatment. Based on TB treatment conditions that have a long duration of drug administration and many types of drugs, there will be a high risk of side effects or toxicity. The purpose of this study was to determine the description of side effects arising from TB drugs at the Bandung City Hospital and the factors causing the incidence of side effects during TB treatment. This research method the author uses a descriptive observational method with a cross sectional approach. The sampling technique uses purposive sampling based on inclusion criteria with a minimum sample of 34 and excursion criteria for TB patients with sepsis complications. The results of the comparative test obtained a p-value of 0.549 > 0.05 which showed that there was no significant difference between the side effects of the drug that arose in new patients and relapse patients.